Possible Fingerprints of Low-intensity, Multiple Impacts in the Magnetic Fabric of some Carbonaceous Chondrites - Balázs Bradák; Yusuke Seto; Sena Toyonaga; Ákos Kereszturi; Martin Chadima (Studia Geophysica et Geodaetica, 2026)

Experimental constraints on the shock history of CI chondrites and Ryugu grains - Toru Nakahashi; Masaaki Miyahara; Akira Yamaguchi; Takamichi Kobayashi; Hitoshi Yusa; Masashi Miyakawa; Naotaka Tomioka; Yuto Takaki; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; et al. (Earth and Planetary Science Letters, 2025)

In situ observation of shock-induced structural evolution of calcite - Yuhei Umeda; Norimasa Ozaki; Toshimori Sekine; Yoichiro Hironaka; Yuichi Inubushi; Kento Katagiri; Ryosuke Kodama; Kohei Miyanishi; Hirotaka Nakamura; Tomoko Sato; Yusuke Seto; Keiichi Sueda; et al. (Physics and Chemistry of Minerals, 2025)
In this study, we aimed to evaluate the shock-induced behavior of calcite (CaCO 3 ), a potential source of CO and/or CO 2 . To this end, we experimentally investigated the time evolution of calcite during shock compression and decompression processes at shock pressures up to 234 ± 19 GPa using an ultrafast time-resolved X-ray diffraction (XRD) coupled with a laser-driven shock compression system. The XRD analysis of shocked calcite showed that the amorphization occurred in the shock compression stage at pressures above 86 ± 7 GPa, and that the decomposition reaction, i.e., CaCO 3 = CaO + CO 2 , was not observed in the decompression stage within the nanosecond timescale. This observation indicated that in addition to pressure and temperature, the shock duration (reaction time) is also a critical factor affecting shock-induced structural changes, such as amorphization and decomposition. Furthermore, the nanosecond laser shock employed in this study may be applied to enhance understanding regarding the impact phenomena of micrometer to submillimeter sized projectiles. The present results suggest that the shock-induced decomposition of calcite does not occur during micrometeorite impacts.

Corrigendum to “Origin of minerals in åkermanite-rich patch texture and oxygen isotopic evolution of compact Type A Ca-Al-rich inclusions from the Northwest Africa 7865 CV chondrite” [Geochim. Cosmochim. Acta 303 (2021) 51–65] - Akimasa Suzumura; Noriyuki Kawasaki; Yusuke Seto; Hisayoshi Yurimoto; Shoichi Itoh (Geochimica et Cosmochimica Acta, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Phase transition and melting in zircon by nanosecond shock loading - Sota Takagi; Kouhei Ichiyanagi; Atsushi Kyono; Nobuaki Kawai; Shunsuke Nozawa; Norimasa Ozaki; Yusuke Seto; Takuo Okuchi; Souma Nitta; Satoru Okada; Kohei Miyanishi; Keiichi Sueda; et al. (Physics and Chemistry of Minerals, 2022)

Theoretical and experimental evidence for the post-cotunnite phase transition in zirconia at high pressure - Daisuke Nishio-Hamane; Haruhiko Dekura; Yusuke Seto; Takehiko Yagi (Physics and Chemistry of Minerals, 2015)

Superior solid solubility of MnSiO3 in CaSiO3 perovskite - Lin Li; Takaya Nagai; Yusuke Seto; Kiyoshi Fujino; Jun Kawano; Shoich Itoh (Physics and Chemistry of Minerals, 2015)

Fate of carbonates within oceanic plates subducted to the lower mantle, and a possible mechanism of diamond formation - Yusuke Seto; Daisuke Hamane; Takaya Nagai; Kiyoshi Fujino (Physics and Chemistry of Minerals, 2008)